An overview of Microfilariae on patients who have received treatment in Batuah Village, Kotawaringin Timur District 2015 - Dian Nurmansyah; Muhammad Fahmi; Rifqoh Rifqoh; Puspawati Puspawati; Putri Kartika Sari; Muhammad Arsyad; Aldiana Astuti (Balai Litbangkes Tanah Bumbu, 2018)
Filariasis is a chronic infectious disease, caused by filarial worms in the lymph and lymph nodes cause lymphangitis and elephantiasis. Batuah Village is the area in Sampit with the largest percentage of microfilariae compared to the surrounding area. From 196 the number of Batuah villagers examined by the filariasis elimination officer of Kotawaringin Timur District Health Office in 2013 obtained 5 positive cases of filariasis with 2.55% microfilaria number which is dominated by filaria worm Brugia malayi. From the local health center has also conducted a mass drug treatment program with DEC medication, combined with albendazole for 12 days on 14-16 July 2014. The aim of this study was to determine the success rate of treatment conducted by the health officer against filariasis patients in the Batuah village. The method used in this microfilariae examination is a microscopic method. Capillary blood was taken on 4 filarial patients who tested positive on the previous examination who had been given DEC + Albendazole treatment, the result from 4 samples that examined 1 positive sample of 4 patients. The implementation of medication that has been done by public health office was successful because there was a decrease of microfilaria rate which was previously 2.55% to 0,51% (<1%).